Fast Photothermoelectric Response in CVD‐Grown PdSe2 Photodetectors with In‐Plane Anisotropy. (11th July 2021) - Li, Gang; Yin, Shiqi; Tan, Chaoyang; Chen, Lijie; Yu, Mengxi; Li, Liang; Yan, Feng
Abstract: PdSe2, a star photosensitive functional material, has been successfully used in photodetectors based on sensing mechanisms of photogating, photoconductive, and photovoltaic effects. Here, a photothermoelectric (PTE) effect is observed in photodetectors based on PdSe2 flakes grown by chemical vapor deposition. The unique photoresponse arises from an electron temperature gradient instead of electron–hole separation. Direct evidence of the PTE effect is confirmed by a nonlocal photoresponse under zero bias. Moreover, the PdSe2 photodetector shows high performance in terms of ultrafast response speed (4 µs), high air‐stability, broadband spectrum photodetection, reasonable responsivity, and anisotropic optical response. This study paves a new way for developing high‐performance photodetectors based on PdSe2 layered materials. Abstract : A photothermoelectric effect in 2D material PdSe2 with high anisotropy is revealed through scanning photocurrent microscopy measurement at zero bias. Performance parameters based on the photothermoelectric effect are investigated experimentally, including response speed, air‐stability, broadband spectrum response, reasonable responsivity, and polarization‐resolved optical response. An ultrafast response speed (≈4 µs) and anisotropic photoresponse with a ratio up to ≈1.3 are observed.